2020
DOI: 10.14453/aabfj.v14i3.6
|View full text |Cite
|
Sign up to set email alerts
|

CSR and Performance of Family Businesses: A Systematic Review

Abstract: There have been numerous studies on the relationship between CSR and performance of family businesses. However, academia have yet to come to a consensus regarding the sign and size of the relationship. Neither was there any consistent evidence on the boundary conditions for the relationship between CSR and performance in family businesses. Based on a review of Agency Theory, Stakeholder Theory, Stewardship Theory, Utilitarian Theory and Social Emotional Wealth Theory, this paper addresses the aforementioned re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 34 publications
(58 reference statements)
0
8
0
Order By: Relevance
“…Hospitality family firms have conducted CSR initiatives to protect their credit ratings and further foster a positive corporate image (Singal, 2014). The previous literature has suggested that founding families prefer going beyond simple business operations by promoting CSR practices to achieve a better family reputation (Gavana et al, 2017;Lv et al, 2020). In light of this, and to untangle the mechanism of the CSR-FP link better, the current study examines how the founding family that own, manage and/or control a firm influences this link.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Hospitality family firms have conducted CSR initiatives to protect their credit ratings and further foster a positive corporate image (Singal, 2014). The previous literature has suggested that founding families prefer going beyond simple business operations by promoting CSR practices to achieve a better family reputation (Gavana et al, 2017;Lv et al, 2020). In light of this, and to untangle the mechanism of the CSR-FP link better, the current study examines how the founding family that own, manage and/or control a firm influences this link.…”
Section: Introductionmentioning
confidence: 96%
“…yes or no) without separating family firm corporate governance structures or with using family ownership alone (Kallmuenzer and Peters, 2018;Masset et al, 2019;Singal, 2014). Different family firm corporate governance structures can impact strategic decision in various processes, such as management, voting and/or supervising (Lv et al, 2020). Therefore, the CSR decision can be an essential strategic decision for hospitality and tourism firms (Kang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…From a theoretical perspective, as stated by the Stakeholder Theory, beyond shareholders a company's relationships with a wider range of stakeholders, including customers, governments, employees, environmentalists, and others, serve as a guide to comprehend the firm's range of obligations (Lv et al, 2020). In this line of thought, a contractual relationship is supposed to exist between the company and all its stakeholders, which makes it possible for businesses to be managed for the benefit of all stakeholders, in the financial and non-financial areas (Jain et al, 2016).…”
Section: Csr and Firm Performancementioning
confidence: 99%
“…The analysis of the relationship between CSR and performance has generated enormous interest among academics lately (Beck et al, 2018;Lv et al, 2020;Partalidou et al, 2020;Úbeda-García et al, 2021). Although in most cases, the previous research demonstrates a direct and positive link (Beck et al, 2018;Busch & Friede, 2018;Jang et al, 2019;Nyeadi et al, 2018;Partalidou et al, 2020;Úbeda-García et al, 2021).…”
Section: Csr and Firm Performancementioning
confidence: 99%
“…The host community of the company occupies a central place in organisational culture and determines the firms' performance in the long run (Nasieku, Togun, & Olubunmi, 2014) Extant studies suggest that large firms, because of their higher capital ratio and more female and minority directors, practice CSR more than the small firms (Cornett, Erhemjamts, & Tehranian, 2014). Even though there have been many studies on the relationship between CSR and firms' performance, there is no consensus regarding the relationship's sign and size (Lv, Li, & Mitra, 2020). Siddiq and Javed (2012) posit that some firms focus on community growth but ignores internal factors and argues that it is difficult to expect CSR from firms because CSR activities may not influence performance.…”
Section: Introductionmentioning
confidence: 99%